Adherence to Mediterranean diet and its associations with circulating cytokines, musculoskeletal health and incident falls in community-dwelling older men: The Concord Health and Ageing in Men Project. Issue 12 (December 2021) - Cervo, Mavil May C.; Scott, David; Seibel, Markus J.; Cumming, Robert G.; Naganathan, Vasi; Blyth, Fiona M.; Le Couteur, David G.; Handelsman, David J.; Ribeiro, Rosilene V.; Waite, Louise M.; Hirani, Vasant
Summary: Background & aims: Mediterranean dietary patterns may exert favourable effects on various health conditions. This study aimed to determine associations of adherence to Mediterranean diet as well as its components, with circulating cytokine levels, musculoskeletal health and incident falls in community-dwelling older men. Methods: Seven hundred ninety-four (794) community-dwelling men with mean age 81.1 ± 4.5 years, who participated in the five-year follow-up of the Concord Health and Ageing in Men Project (CHAMP) were included in the cross-sectional analysis, and 616 attended follow-up three years later. Adherence to Mediterranean diet was assessed using MEDI-LITE (literature-derived Mediterranean diet) score which was obtained using a validated diet history questionnaire. Twenty-four evaluable circulating cytokines were analyzed using Bio-Plex Pro Human Cytokine 27-plex Assay kit. Appendicular lean mass (ALM) and bone mineral density (BMD) were measured using dual-energy x-ray absorptiometry (DXA). Three-year changes in gait speed and hand grip strength were assessed by walking a 6-m course and using a dynamometer respectively and analyzed using linear mixed-effects models. Incident falls over three years were determined through telephone interviews every four months. Multivariable linear regression was utilized to determine the cross-sectional associations between MEDI-LITE scores and circulating cytokines, bone mineral density, ALM, and ALMBMI . Linear mixed-effects models were performed to estimate associations between MEDI-LITE scores and three-year change in hand grip strength and gait speed while negative binomial regression was applied to estimate associations between MEDI-LITE scores and three-year incident falls as well as associations between each MEDI-LITE component and three-year incident falls. Adjustments for multiple comparisons were performed using Benjamini-Hochberg adjustment for multiple testing. Results: A higher MEDI-LITE score, indicating greater adherence to Mediterranean diet, was associated with higher appendicular lean mass adjusted for body mass index (ALMBMI ) (β: 0.004 kg; 95% CI: 0.000, 0.008), and lower incident falls rates (IRR: 0.94; 95% CI: 0.89, 0.99). Higher consumption of monounsaturated fatty acids (IRR: 0.76; 95% CI: 0.59, 0.98) and monounsaturated fatty acids to saturated fatty acids ratio (IRR: 0.72; 95% CI: 0.57, 0.90) were associated with 24%, and 28% lower falls risk in older men respectively. MEDI-LITE scores were not associated with BMD or physical function parameters. Conclusions: Adherence to a Mediterranean diet is associated with higher ALMBMI, and fewer falls in community-dwelling older men. Monounsaturated and saturated fatty acids were the most important contributors to the association between Mediterranean diet and falls risk.